Development of Digital Flipbook Media for Smart Fathers, Parenting - Nur Riska; Irma Yuliantina; Karima Salihanisa; Dhea Yuwono Putri; Syifa Andina; Dwi Purwestri Sri Suwarningsih; Yuli Yana; Lucy Herny (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
This research aims to develop and test the feasibility of learning media based on flipbook digital with the theme "Smart Fathers Raising Children". The development model used is ADDIE, which consists of five stages: (1)Analysis, analyzing fathers' needs in child care and family literacy problems; (2)Design, designing material structure, illustrations, and features flipbook digital according to user needs; (3)Development, developing media using software Heyzine to produce a product ready for testing; (4) Implementation, testing the media on a limited basis with fathers as the main users; and (5)Evaluation, evaluate the father's response and make revisions to improve the media. Mediaflipbook digital. This program presents informative content, interactive visuals, and easy-to-understand narratives to improve fathers' understanding and parenting literacy. Tests with fathers showed a 90.8% response rate, which is considered very strong and positive. Therefore, the flipbook digital" Smart Fathers Raise Children" is declared very suitable for use as a family learning medium to support the role of fathers in raising children.